Correlation Between Bladder Pain Syndrome/Interstitial Cystitis and Pelvic Inflammatory Disease. Issue 46 (November 2015) - Chung, Shiu-Dong; Chang, Chao-Hsiang; Hung, Peir-Haur; Chung, Chi-Jung; Muo, Chih-Hsin; Huang, Chao-Yuan
Abstract : Abstract: Pelvic inflammatory disease (PID) has been investigated in Western countries and identified to be associated with chronic pelvic pain and inflammation. Bladder pain syndrome/interstitial cystitis (BPS/IC) is a complex syndrome that is significantly more prevalent in women than in men. Chronic pelvic pain is a main symptom of BPS/IC, and chronic inflammation is a major etiology of BPS/IC. This study aimed to investigate the correlation between BPS/IC and PID using a population-based dataset. We constructed a case–control study from the Taiwan National Health Insurance program. The case cohort comprised 449 patients with BPS/IC, and 1796 randomly selected subjects (about 1:4 matching) were used as controls. A Multivariate logistic regression model was constructed to estimate the association between BPS/IC and PID. Of the 2245 sampled subjects, a significant difference was observed in the prevalence of PID between BPS/IC cases and controls (41.7% vs 15.4%, P < 0.001). Multivariate logistic regression analysis revealed that the odds ratio (OR) for PID among cases was 3.69 (95% confidence interval [CI]: 2.89–4.71). Furthermore, the ORs for PID among BPS/IC cases were 4.52 (95% CI: 2.55–8.01), 4.31 (95% CI: 2.91–6.38), 3.00 (95% CI: 1.82–4.94), and 5.35 (95% CI: 1.88–15.20) in the <35, 35–49, 50–64, and >65 years age groups, respectively, after adjusting for geographic region, irritable bowel syndrome, and hypertension. Joint effect was also noted, specifically when patients had both PID and irritable bowel disease with OR of 10.5 (95% CI: 4.88–22.50). This study demonstrated a correlation between PID and BPS/IC. Clinicians treating women with PID should be alert to BPS/IC-related symptoms in the population.